2019
DOI: 10.1002/slct.201803056
|View full text |Cite
|
Sign up to set email alerts
|

Nozzle‐Less Electrospun Nitrogen‐Doped Hollow Carbon Nanofibers as Enhanced Sensing Platform for Carbendazim Electrochemical Detection

Abstract: Nitrogen‐doped hollow carbon nanofibers (N‐HCNFs) synthesized by nozzle‐less electrospinning were directly obtained, showing a rough surface and hollow structure. The as‐prepared N‐HCNFs exhibit excellent electrocatalytic activity, good stability and low detection limit, which is a promising alternative applications in environmental protection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…N-doped CNFs fabricated by nozzle-less electrospinning were used for electrochemical sensing of carbendazim. 137 This sensor has good stability and high sensitivity for the detection of carbendazim in 0.1 mol/L PBS. The studies showed the linear relation with regression equation I p = 0.891C + 3.37 and a detection limit of 0.053 (S/N = 3).…”
Section: Detection Of Food Preservativesmentioning
confidence: 99%
See 1 more Smart Citation
“…N-doped CNFs fabricated by nozzle-less electrospinning were used for electrochemical sensing of carbendazim. 137 This sensor has good stability and high sensitivity for the detection of carbendazim in 0.1 mol/L PBS. The studies showed the linear relation with regression equation I p = 0.891C + 3.37 and a detection limit of 0.053 (S/N = 3).…”
Section: Detection Of Food Preservativesmentioning
confidence: 99%
“…The sensors’ storage stability was also investigated, and only a slight current decrease (∼2.8%) was observed after the electrode was stored for 15 days at room temperature. N-doped CNFs fabricated by nozzle-less electrospinning were used for electrochemical sensing of carbendazim . This sensor has good stability and high sensitivity for the detection of carbendazim in 0.1 mol/L PBS.…”
Section: Carbon Nanofiber-based Sensor Applicationsmentioning
confidence: 99%
“…Other hard templates included ZnO [120], SnO 2 /Fe 2 O 3 [121], and PS microspheres [122]. Several soft templates have been also proposed to obtain hollow carbon nanofibers [123], together with triple-co-axial electrospinning, nozzle-less electrospinning, and other approaches [124][125][126].…”
Section: Electrospinning Of Hollow Carbon Nanofibersmentioning
confidence: 99%
“…The prepared sensor can detect atrazine at trace levels in spiked real-time water samples. Yang et al [107] also synthesized nitrogen-doped hollow carbon nanofibers (N-HCNFs) by nozzle-less electrospinning for carbendazim detection. Table 3 summarizes the properties and performances of various non-enzyme electrochemical sensors based on electrospinning.…”
Section: Non-enzyme Electrochemical Sensorsmentioning
confidence: 99%